Semantics of Magic Items in Uzbek Folk Tales - Zebiniso Rasulova (Researchparks Publishing, 2022)
In fairy tales, magical objects are used to reveal some secret related to the fate of a person or the natural world (through magic stones, love spells, magic apples, etc.), to destroy evil (for example, using a magic comb or a magic mirror to destroy a creeping villain , punishing deceitful and evil creatures with a club for whipping), to manifest high human desires, such as alleviating the torment of hard work, to achieve a peaceful and comfortable life (with the help of an open tablecloth, a hot pot, a bin, a flying carpet, etc.). The article deals with the semantics of enchanted objects.